Trends and variability in surface ozone over the United States. Issue 17 (14th September 2015) - Strode, Sarah A.; Rodriguez, Jose M.; Logan, Jennifer A.; Cooper, Owen R.; Witte, Jacquelyn C.; Lamsal, Lok N.; Damon, Megan; Van Aartsen, Bruce; Steenrod, Stephen D.; Strahan, Susan E.
Abstract We investigate the observed trends and interannual variability in surface ozone over the United States using the Global Modeling Initiative chemical transport model. We discuss the roles of meteorology, emissions, and transport from the stratosphere in driving the interannual variability in different regions and seasons. We demonstrate that a hindcast simulation for 1991–2010 can reproduce much of the observed variability and the trends in summertime ozone, with correlation coefficients for seasonally and regionally averaged median ozone ranging from 0.46 to 0.89. Reproducing the interannual variability in winter and spring in the western United States may require higher‐resolution models to adequately represent stratosphere‐troposphere exchange. Hindcast simulations with fixed versus variable emissions show that changes in anthropogenic emissions drive the observed negative trends in monthly median ozone concentrations in the eastern United States during summer, as well as the observed reduction in the amplitude of the seasonal cycle. The simulation underestimates positive trends in the western United States during spring, but excluding the first 4 years of data removes many of the statistically significant trends in this region. The reduction in the slope of the ozone versus temperature relationship before and after major emission reductions is also well represented by the model. Our results indicate that a global model can reproduce many of the important features of the meteorologically induced ozone variability as well as the emission‐driven trends, lending confidence to model projections of future changes in regional surface ozone.